Prevalence, determinants and clinical correlates of vitamin D deficiency in patients with Chronic Obstructive Pulmonary Disease in London, UK. Issue 175 (January 2018) - Jolliffe, David A.; James, Wai Yee; Hooper, Richard L.; Barnes, Neil C.; Greiller, Claire L.; Islam, Kamrul; Bhowmik, Angshu; Timms, Peter M.; Rajakulasingam, Raj K.; Choudhury, Aklak B.; Simcock, David E.; Hyppönen, Elina; et al.
Highlights: Vitamin D deficiency is common among UK adults with chronic obstructive pulmonary disease. Classical environmental determinants of vitamin D status operate in this population. Vitamin D status associated with clinical markers of lung function. Genetic variation in the vitamin D pathway did not influence vitamin D status or measures of COPD severity. Abstract: Vitamin D deficiency is common in patients with chronic obstructive pulmonary disease (COPD), yet a comprehensive analysis of environmental and genetic determinants of serum 25-hydroxyvitamin D (25[OH]D) concentration in patients with this condition is lacking. We conducted a multi-centre cross-sectional study in 278 COPD patients aged 41–92 years in London, UK. Details of potential environmental determinants of vitamin D status and COPD symptom control and severity were collected by questionnaire, and blood samples were taken for analysis of serum 25(OH)D concentration and DNA extraction. All participants performed spirometry and underwent measurement of weight and height. Quadriceps muscle strength (QS) was measured in 134 participants, and sputum induction with enumeration of lower airway eosinophil and neutrophil counts was performed for 44 participants. Thirty-seven single nucleotide polymorphisms (SNP) in 11 genes in the vitamin D pathway ( DBP, DHCR7, CYP2R1, CYP27B1, CYP24A1, CYP27A1, CYP3A4, LRP2, CUBN, RXRA, and VDR ) were typed using Taqman allelic discrimination assays. Linear regression was used to identify environmental and genetic factors independently associated with serum 25(OH)D concentration and to determine whether vitamin D status or genetic factors independently associated with % predicted forced expiratory volume in one second (FEV1 ), % predicted forced vital capacity (FVC), the ratio of FEV1 to FVC (FEV1 :FVC), daily inhaled corticosteroid (ICS) dose, respiratory quality of life (QoL), QS, and the percentage of eosinophils and neutrophils in induced sputum. Mean serum 25(OH)D concentration was 45.4 nmol/L (SD 25.3); 171/278 (61.5%) participants were vitamin D deficient (serum 25[OH]D concentration <50 nmol/L). Lower vitamin D status was independently associated with higher body mass index (P = 0.001), lower socio-economic position (P = 0.037), lack of vitamin D supplement consumption (P < 0.001), sampling in Winter or Spring (P for trend = 0.006) and lack of a recent sunny holiday (P = 0.002). Vitamin D deficiency associated with reduced % predicted FEV1 (P for trend = 0.060) and % predicted FVC (P for trend = 0.003), but it did not associate with FEV1 :FVC, ICS dose, QoL, QS, or the percentage of eosinophils or neutrophils in induced sputum. After correction for multiple comparisons testing, genetic variation in the vitamin D pathway was not found to associate with serum 25(OH)D concentration or clinical correlates of COPD severity. Vitamin D deficiency was common in this group of COPD patients in the UK, and it associated independently with reduced % predicted FEV1 and FVC. However, genetic variation in the vitamin D pathway was not associated with vitamin D status or severity of COPD.